Adjusting microbiome profiles for differences in microbial load by spike-in bacteria. Issue 1 (December 2016) - Stämmler, Frank; Gläsner, Joachim; Hiergeist, Andreas; Holler, Ernst; Weber, Daniela; Oefner, Peter; Gessner, André; Spang, Rainer
Abstract Background Next-generation 16S ribosomal RNA gene sequencing is widely used to determine the relative composition of the mammalian gut microbiomes. However, in the absence of a reference, this does not reveal alterations in absolute abundance of specific operational taxonomic units if microbial loads vary across specimens. Results Here we suggest the spiking of exogenous bacteria into crude specimens to quantify ratios of absolute bacterial abundances. We use the 16S rDNA read counts of the spike-in bacteria to adjust the read counts of endogenous bacteria for changes in total microbial loads. Using a series of dilutions of pooled faecal samples from mice containing defined amounts of the spike-in bacteriaSalinibacter ruber, Rhizobium radiobacter andAlicyclobacillus acidiphilus, we demonstrate that spike-in-based calibration to microbial loads allows accurate estimation of ratios of absolute endogenous bacteria abundances. Applied to stool specimens of patients undergoing allogeneic stem cell transplantation, we were able to determine changes in both relative and absolute abundances of various phyla, especially the genusEnterococcus, in response to antibiotic treatment and radio-chemotherapeutic conditioning. Conclusion Exogenous spike-in bacteria in gut microbiome studies enable estimation of ratios of absolute OTU abundances, providing novel insights into the structure and the dynamics of intestinal microbiomes.